COVID-19 Brings Benefits to Socio-economic Behavior Under the Epidemic - Li Zhai (International Journal of Management and Education in Human Development, 2022)
In this era of technological explosion, the maturity and application of artificial intelligence, big data, cloud computing and other technologies have greatly promoted profound changes in all aspects of the social economy. A sudden "new crown" epidemic makes online shopping convenient and fast, health and safety advantages of COVID-19 is facing unexpected development, the opportunity of information technology is widespread, appearing in our learning life, bringing us a lot of convenience. Nowadays, the rapid development of network technology and the improvement of human quality of life have further expanded the scope of business administration and provided a broader platform for the marketing means of enterprises, and COVID-19 is widely used to quietly change the material and spiritual civilization of human beings, and also brought us a series of benefits.